2016
DOI: 10.1097/qai.0000000000000927
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine Monotherapy-Based cART Is Efficacious for HBV Treatment in HIV/HBV Coinfection When Baseline HBV DNA <20,000 IU/mL

Abstract: Background Although combination antiretroviral therapy (cART) including tenofovir (TDF)+lamivudine (3TC) or emtricitabine (FTC) is recommended for treatment of HIV/HBV co-infected patients, TDF is unavailable in some resource-limited areas. Some data suggest that 3TC monotherapy-based cART may be effective in patients with low pre-treatment HBV DNA. Methods Prospective study of 151 Chinese HIV/HBV co-infected subjects of whom 60 received 3TC-based cART and 91 received TDF+3TC-based cART. Factors associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 22 publications
2
22
1
Order By: Relevance
“…Indeed, our data showed that 26.1% of the coinfected patients had a HBV viral load >20,000 UI/mL. This finding is in line with what was found in another study conducted in developing countries, where a significant proportion of HIV/HBV coinfected patients present HBV DNA≥ 20,000 IU/mL [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, our data showed that 26.1% of the coinfected patients had a HBV viral load >20,000 UI/mL. This finding is in line with what was found in another study conducted in developing countries, where a significant proportion of HIV/HBV coinfected patients present HBV DNA≥ 20,000 IU/mL [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…3TC is a backbone option of first line ART regimen, globally recommended and recognized as well tolerated and active against both HIV and HBV [ 47 ]. Prior studies have shown that coinfected people with lower HBV DNA levels (<20,000 IU/mL) or who are HBeAg-negative, can be considered for 3TC monotherapy, when TDF is not readily available or is contraindicated [ 44 ] Briefly, no genetic mutations related to HBV resistance to 3TC were found in the S Ag nor in RT genes. In contrast to our finding, recent studies conducted in northern Mozambique and in other sub-Saharan countries found mutations associated with primary HBV resistance to 3TC [ 28 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…As is known, the emergence of HBV drug‐resistant mutations in HIV/HBV co‐infected patients who are on ART including 3TC and/or TDF is common . At 24 months, a very low prevalence (1.9%) of 3TC resistance was found in this study, compared to Gu L's report which indicated 16.0% of the patients harboured 3TC‐resistant mutants after 96‐week treatment .…”
Section: Discussioncontrasting
confidence: 49%
“…Fortunately, virological and immunological responses to ART were not affected by HBV coinfection status among Chinese patients [30]. In terms of treatment, prior to widespread availability of TDF through NFATP, the efficacy of using a regimen that included only one active agent (3TC) for HBV coverage was demonstrated among Chinese patients in a study by Li and colleagues, and 3TC alone could be considered for HBV coverage in HIV/ HBV coinfected patients when baseline HBV DNA levels are lower than 20,000 IU/mL, providing a feasible treatment option in resource-limited settings [31]. The current recommendation is to select a HAART regimen that includes two drugs with anti-HBV activity.…”
Section: Promoting Multidisciplinary Care and Integrating The Hiv/aidmentioning
confidence: 99%